2018
DOI: 10.1088/1361-648x/aabdfe
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quasiparticle calculation of x-ray photoelectron spectra of solids

Abstract: It has been highly desired to provide an accurate and reliable method to calculate core electron binding energies (CEBEs) of crystals and to understand the final state screening effect on a core hole in high resolution x-ray photoelectron spectroscopy (XPS), because the ΔSCF method cannot be simply used for bulk systems. We propose to use the quasiparticle calculation based on many-body perturbation theory for this problem. In this study, CEBEs of band-gapped crystals, silicon, diamond, β-SiC, BN, and AlP, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 42 publications
(58 reference statements)
0
50
2
Order By: Relevance
“…For example, for some simple molecules, such as NH 3 and N 2 H 4 , the calculated values differ by -0.9 eV and -1.28 eV from experimental data, respectively. Another method for calculating absolute core-electron binding energies in extended systems is based on the GW approach [29]. However, the high computational cost of GW calculations makes its application to chemically complex systems challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for some simple molecules, such as NH 3 and N 2 H 4 , the calculated values differ by -0.9 eV and -1.28 eV from experimental data, respectively. Another method for calculating absolute core-electron binding energies in extended systems is based on the GW approach [29]. However, the high computational cost of GW calculations makes its application to chemically complex systems challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The first property is that the excitation spectra such as XPS, XAS, and XES can be directly treated by solving the Dyson equation or the Bethe-Salpeter equation (BSE) [27][28][29][30][31][32][33] in manybody perturbation theory. In fact, recent ab initio studies using the Green's function approach showed the accurate prediction of core electron binding energy in XPS simulations [34][35][36] . Especially, the GW+Bethe-Salpeter equation (GW + BSE) method has been widely used for simulating the XAS spectra in molecule, cluster, and solid systems [37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure calculations in quantum chemistry usually use the Gaussian basis functions which are not always suited to represent the excited state wave functions with screening effect owing to its basis set incompleteness. To overcome the basis set incompleteness, we apply the all-electron mixed basis functions 49 for the quasiparticle wave functions, which have been used successfully in our previous study 34 . Using this approach, we can keep the accuracy of the GW + BSE method with the all-electron mixed basis functions for simulating XES spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The first exploratory studies for solid-state systems obtained partly promising results. 39 , 40 The few existing studies for molecular core excitations also give a mixed first impression, as anything between a 0.5 18 and 10 eV deviation from experiment has been reported. 31 , 41 In this work, we show how reliable and highly accurate core-level BEs can be obtained from GW and explain why large deviations from experiment were previously reported.…”
mentioning
confidence: 99%